Interferon Gamma Induces the Increase of Cell-Surface Markers (CD80/86, CD83 and MHC-II) in Splenocytes From Atlantic Salmon - Morales-Lange, Byron; Ramírez-Cepeda, Felipe; Schmitt, Paulina; Guzmán, Fanny; Lagos, Leidy; Øverland, Margareth; Wong-Benito, Valentina; Imarai, Mónica; Fuentes, Derie; Boltaña, Sebastián; Alcaíno, Javier; Soto, Carlos; et al. (Frontiers in Immunology, 2021)
Type II interferon gamma (IFNγ) is a pleiotropic cytokine capable of modulating the innate and adaptive immune responses which has been widely characterized in several teleost families. In fish, IFNγ stimulates the expression of cytokines and chemokines associated with the pro-inflammatory response and enhances the production of nitrogen and oxygen reactive species in phagocytic cells. This work studied the effect of IFNγ on the expression of cell-surface markers on splenocytes of Atlantic salmon (Salmo salar). In vitro results showed that subpopulations of mononuclear splenocytes cultured for 15 days were capable of increasing gene expression and protein availability of cell-surface markers such as CD80/86, CD83 and MHC II, after being stimulated with recombinant IFNγ. These results were observed for subpopulations with characteristics associated with monocytes (51%), and features that could be related to lymphocytes (46.3%). In addition, a decrease in the expression of zbtb46 was detected in IFNγ-stimulated splenocytes. Finally, the expression of IFNγ and cell-surface markers was assessed in Atlantic salmon under field conditions. In vivo results showed that the expression of ifnγ increased simultaneously with the up-regulation of cd80/86, cd83 and mhcii during a natural outbreak of Piscirickettsia salmonis. Overall, the results obtained in this study allow us to propose IFNγ as a candidate molecule to stimulate the phenotypic progression of a small population of immune cells, which will increase antigen presenting cells markers. Thereby, modulatory strategies using IFNγ may generate a robust and coordinated immune response in fish against pathogens that affect aquaculture.